Pengaruh Literasi Keuangan dan Teknologi Keuangan terhadap Kepuasan Keuangan di Mediasi oleh Perilaku Keuangan pada Guru Ekonomi Se-Jawa Tengah - Litta Wardhatul Khamro; Aniek Hindrayani; Leny Noviani (Journal on Education, 2023)
This research is a quantitative research with a sampling technique using purposive sampling with the respondent's criteria, namely Economics teachers from Central Java who use financial technology. Data was collected by distributing online google form questionnaires and then distributing them through the Central Java MGMP group. This study used 117 respondents. The data obtained is then processed with the help of SPSS 26 to test the validity, reliability, classic assumption test, hypothesis test, and t test. The results of research data processing show (1) Financial literacy has no significant effect on financial satisfaction, this is evidenced by the significance value obtained, namely 0.323> 0.05 (2) Financial technology has a significant effect on financial satisfaction, as evidenced by a significance result of 0.023 < 0.05, (3) Financial literacy has no significant effect on financial satisfaction through financial behavior, this can be seen from the direct effect value of -0.168 which is smaller than the indirect effect of 0.042, (4) Financial technology influences financial satisfaction through behavior financial, al is evidenced by the value of the direct effect of 0.283 greater than the indirect effect of 0.053.